IMPLEMENTATION OF MOTORCYCLE SECURITY EQUIPMENT USING RFID BASED ARDUINO UNO E-KTP - Ahdika Dafiq Mafaja Yoni; Nasrulloh Nasrulloh; Edmund Ucok Armin (Journal of Electronic and Electrical Power Applications, 2022)
During a pandemic like now, many workers are being expelled by the company, resulting in a decline in the economy in various regions. To meet the needs of a person may do bad things such as curanmor (motorcycle theft). Even though the motorbike is equipped with a fairly strict security system, it is still sometimes broken by thieves. This study aims to create a motor vehicle security system based on Arduino R3 and RFID as an e-KTP sensor. Where this system can turn on or turn off the motorbike using an ID card or using its RFID Pin. even though the thief managed to break into the ignition, the motor still couldn't start because it needed other access. Based on the results of observations and tests carried out, the authors can conclude that the performance of the motorcycle safety device system using e-KTP works quite well. When the contact is on, it will activate the safety device system before activating the motor electrical system. RFID needs access to the appropriate e-KTP and is forwarded to the microcontroller (Arduino) then produces output to the relay to turn on the motor's electricity so that the motor can be turned on/started